WORD FORMATION PROCESSES USED BY WORD FORMATION PROCESSES OF REGISTERS USED BY BRAWIJAYA CHESS CLUB OF REGISTERS BRAWIJAYA CHESS CLUB - KURNIAH, SUCI INDRA (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Word Formation Processes, Registers, Brawijaya Chess Club.Sociolinguistics is the study related to the language and society. In sociolinguistics, we know the concept of register. Register is another complicatingfactor in any study of language varieties. Registers are sets of language itemsassociated with discrete occupational or social group. Thus the result of register in this study also found word formation processes. In this case, the writer isinterested in studying the registers used by Brawijaya Chess Clubs and wordformation processes. There are three problems of the study, namely: (1) What are the register used by Brawijaya Chess Club?(2) What are the meaning of register used by Brawijaya Chess Club?and (3) What are the word formation processes of the register used by Brawijaya Chess Club?This studyused qualitative research which has aims in getting the description about register used by Brawijaya Chess Club.The data of this study was taken in the form of utterance containing of register used by Brawijaya Chess Club.In this study, the writer observed 15 members and 3 national mastershad an interviewed of Brawijaya Chess Club to answer those problems of study.This study found 49 registers used by Brawijaya Chess Club.Based on theanalysis, the writer found out that those 49 registers and found 3 types of wordformation process.Type of word formation found are31borrowing, 1 blending and17 multiple processes. The writer suggests the next researchers who are interested in doing research with the same topicabout register to use other interesting objects in the society. The writer hopes to the further researchers to do similar researches on registers with different tehniques, theories and subjects in order to give a contribution to the study of linguistics and it make the sources will be more  various.